'Social enterprise spin-outs': an institutional analysis of their emergence and potential. Issue 8 (3rd August 2018) - Sepulveda, Leandro; Lyon, Fergus; Vickers, Ian
ABSTRACT: The recent phenomenon of public sector ' social enterprise spin-outs ' is examined in order to critically assess their nature and innovative potential as providers of public services. The study utilises a theoretical model of institutional creation and change which incorporates key characteristics of 'corporate spin-outs' and 'university spin-outs' to facilitate the examination of their public sector counterparts, drawing on interview evidence from 30 newly-established social enterprise providers of health and care services in England. A main contribution of the paper is to provide a conceptual framework which sheds light on the strengths and potential vulnerabilities of social enterprise spin-outs as novel organisations that span the public, private and civil society sectors.